Synthesis and characterization of Nd(OH)3-ZnO composites for application in photocatalysis and disinfection - Costa, Sabryna I.G.; Cauneto, Vinícius D.; Fiorentin-Ferrari, Leila D.; Almeida, Priscila B.; Oliveira, Regiane C. [UNESP]; Longo, Elson; Módenes, Aparecido N.; Slusarski-Santana, Veronice (Elsevier, 2020)
Nd(OH)3-ZnO composites were synthesized with three content of Neodymium (1, 3 and 5 wt%) and characterized in terms of their structural, morphological, vibrational, optical, surface, photocatalytic and antimicrobial properties. The Nd(OH)3-ZnO composites are constituted by ZnO, which showed hexagonal structure, three-dimensional morphology analogous to an arrangement of flowers with hexagonal rods, and the Nd(OH)3 in the hexagonal phase with irregularly spherical shape. The presence of the Nd(OH)3 in the composites promoted some structural degree of disorder in the ZnO network as well as interstitial defects and oxygen vacancy, which improved photocatalytic and antimicrobial activity. From the Box-Behnken design and response surface methodology, it was determined that the 1Nd(OH)3-ZnO composite showed the highest photocatalytic activity, which was attributed to its higher crystallinity, smaller crystallite size and particle width, band gap energy close to ZnO and lower recombination rate compared to ZnO. Nd(OH)3-ZnO composites showed higher antimicrobial activity against E. coli and S. aureus than ZnO pure, evidencing the synergistic effect between Nd(OH)3 and ZnO in the composites. Therefore, this study highlights the synthesis of Nd(OH)3-ZnO composites combining zinc oxide and neodymium hydroxide with excellent photocatalytic and antimicrobial activity, which can be used in different practical applications such as luminescent material, photocatalyst and antimicrobial agent.
Keywords: Antimicrobial agent; Box-Behnken design; Hydroxide-oxide interaction; Photocatalyst